Comparative Evaluation of Debris Extrusion, Remaining Dentin Thickness and Fracture Resistance of Endodontically Treated Teeth Using Rotary and Reciprocating Endodontic File Systems: An In Vitro Study (Bangladesh Journal of Medical Science, 2024)
Background: Endodontic treatment aims to thoroughly clean and shape the root canal system while preserving the structural integrity of the tooth. The choice of endodontic file system can significantly impact the outcomes of this procedure. This in vitro study compares debris extrusion, remaining dentin thickness, and fracture resistance in endodontically treated teeth using rotary and reciprocating endodontic file systems.Materials and Methods: Forty extracted human mandibular premolars were selected and randomly divided into two groups (n=20 each): Group A was prepared using a rotary file system, and Group B was prepared using a reciprocating file system. Debris extrusion was quantified using the Myers and Montgomery method, and remaining dentin thickness was measured at the coronal, middle, and apical thirds of each root. Fracture resistance was evaluated using a universal testing machine. The data were analyzed using appropriate statistical tests.Results: The mean debris extrusion in Group A was 0.25 mg, while in Group B, it was 0.18 mg. The remaining dentin thickness in Group A was 1.24 mm, 1.15 mm, and 1.06 mm at the coronal, middle, and apical thirds, respectively, while in Group B, it was 1.30 mm, 1.22 mm, and 1.14 mm. The mean fracture resistance in Group A was 888 N, and in Group B, it was 920 N.Conclusion: The reciprocating endodontic file system exhibited less debris extrusion, slightly greater remaining dentin thickness, and slightly higher fracture resistance compared to the rotary file system, although these differences were not statistically significant. Both file systems can be considered safe and effective for endodontic treatment, with the choice depending on clinician preference and specific clinical scenarios.Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S87-S91